Contractor's portable handbook - Woodson, R. Dodge (McGraw-Hill, 1998)
The take-it-with-you guide to everything you need to know about contracting. This is the most important manual a contractor or construction tradesperson can have. Why? It covers every aspect of planning contracting work, from foundations to plumbing to roofing--while keeping an eye on the bottom line. It addresses questions of law, such as zoning and local code, that are crucial to getting the permits you need to help jobs go smoothly. The book is highly visual, too, packed with crucial formulas and tables. And it comes in a flexible, carry-along format, making it easy to consult on site, in the office, or in the shop. Clear chapter headings and a detailed index take you straight to the information you need on: site work: before, during, and after a job; water supply; well, pump, and sewage systems; footings, foundations, and flooring; ceilings, walls (interior and exterior), trims, doors, and roofing; stairs, windows, and skylights; plumbing, HVAC, and electrical systems; insulation; decks and porches; cabinets and counters; fireplaces and flues; provisions for the physically challenged; essentials of remodelilng; conversion tables and calculation methods.